Effect of Face Mask Wearing on Maternal Oxygen Saturation and on Non-stress Test Results - Udompornthanakij, Pattraporn; Kongsomboon, Kittipong; Hanprasertpong, Tharangrut (Thai Journal of Obstetrics and Gynaecology, 2025)
Objective: This study was conducted to evaluate the maternal oxygen saturation at the 5th minute, as measured by pulse oximetry and non-stress test (NST) results in pregnant women when they are not wearing and wearing a face mask. Materials and methods: A prospective observational study was conducted among pregnant women with a gestational age ≥32 weeks. Each participant was monitored for maternal oxygen saturation, as measured by pulse oximetry, vital signs, and NST for approximately 40 minutes divided into 20-minute durations under conditions of them not wearing and wearing a face mass, respectively. Results: In total, 72 participants were enrolled. The mean maternal oxygen saturation was significantly lower at the 5th minute of monitoring the pregnant women when wearing a face mask than at the 5th minute when not wearing a face mask (mean ± SD = 97.78 ± 1.24 % vs. 98.15 ± 1.12 %, p= 0.009). The mean maternal diastolic blood pressure was also significantly lower at the 5th minute of monitoring participants when wearing a face mask versus not wearing a face mask (mean ± SD = 66.32 ± 7.60 mmHg vs. 68.40± 8.13 mmHg, p= 0.007). Non-reactive NST results are comparable when wearing and not wearing a face mask (p = 0.313). Conclusion: The mean maternal oxygen saturation and maternal diastolic blood pressure were significantly lower at the 5th minute of monitoring the participants when wearing a face mask than at the 5th minute when not wearing a face mask, but the trend was no difference when monitoring for a longer time.